El régimen de la participación electoral de las personas con discapacidad en los cuarenta años de democracia - Gálvez Muñoz, Luis A. (Revista de Derecho Político, 2017)
Resumen: En este trabajo se realiza el estudio, en la perspectiva histórica de los cuarenta años de democracia en España, de las normas que han disciplinado la participación electoral de las personas con discapacidad, en tanto máximo exponente de la integración en la comunidad de este colectivo tan numeroso, variado y vulnerable. Ello permite no solo conocer la regulación existente en los diversos estadios de nuestra joven democracia, sino también, al propio tiempo, poder valorar de manera más completa, junto con otros factores contextuales, la normativa actualmente vigente. La exposición se divide en las tres etapas que parecen más significativas desde el punto de vista de la regulación estudiada: el arranque de la democracia, con la normativa electoral de la época, el Real Decreto Ley 20/1977, de 18 de marzo (periodo de indiferencia); el establecimiento de la Ley Orgánica 5/1985, de 19 de junio, del Régimen Electoral General, y los ajustes y complementos de los años inmediatamente posteriores (periodo de visualización); y los avances normativos producidos con el arranque del siglo xxi, con la muy relevante Convención de Nueva York de Naciones Unidas sobre los derechos de las personas con discapacidad y el Real Decreto 422/2011, de 25 de marzo, por el que se aprueba el Reglamento sobre las condiciones básicas para la participación de las personas con discapacidad en la vida política y en los procesos electorales (periodo de sensibilización). A ello le siguen unas breves consideraciones finales entre recapitulatorias y prospectivas, la principal de las cuales es la de poner de manifiesto la constante y sólida progresión que poco a poco se ha ido produciendo en este terreno con un resultado final que merece ser reconocido y estimado. Se apunta también que la mayoría de las acciones normativas establecidas operan en el campo del derecho de sufragio activo, dejando bastante de lado el derecho de sufragio pasivo y otras formas de participación; que la atención legislativa a los diversos colectivos de personas con discapacidad no ha sido equilibrada ni a lo largo del tiempo ni en el resultado final, observándose, en general, una mayor atención a la problemática de las personas con discapacidad física y sensorial (visual o auditiva) que a las de aquellas con discapacidad intelectual y psíquica; y que son muchos los retos todavía pendientes, como la limitación de la restricción del voto de las personas con discapacidad intelectual y psíquica y la adopción de medidas de apoyo en el terreno del sufragio pasivo. Summary: I. Introduction. II. The start of the democracy (period of indiference). II.1 The Law Royal Decree 20/1977, of March 18, on electoral norms. II.1.1 Provisions on the field of active suffrage. II.1.2 Provisions on the field of passive suffrage. II.1.3 Provisions on others fields. II.2 Other norms. III. The establishment of the loreg and its adjusts and complements during the XXI century (period of visualization). III.1 The LOREG. III.1.1. New elements. III.1.2 Continuity elements. III.2 The posterior adjusts and complements. III.2.1 The accessibility of electoral sites. III.2.2 The vote by mail in case of illness or inability which prevents the displacement. III.2.2.1 Develop of 72.c) article of LOREG in its first version. III.2.2.2 The reform of LOREG in 1992 and the posterior develop. IV. The normative advances produced at the start of the xxi century (period of sensitization). IV.1 The anti-discriminatory movement along the centuries. IV.2 The sectoral norms of disability. IV.2.1 Law 51/2003, of 2 December. IV.2.2 2006 UN Convention on the Rights of Persons with Disabilities. IV.2.3 Law 27/2007, of 23 October. IV.2.4. Royal Legislative Decree 1/2013, of 29 November. IV.3 The electoral norms. IV.3.1 The reforms of LOREG in 2007 and 2011 and the develop normative. IV.3.2 The Royal Decree 422/2011, of 25 March. IV.3.3 Other dispositions. V. Final considerations. Abstract: This work deals with the study, in the historical perspective of the forty years of democracy in Spain, of the norms that have disciplined the electoral participation of people with disabilities, as a maximum exponent of the integration in the community of this so huge, varied and vulnerable collective. This allows not only to know the existing regulation in the various stages of our young democracy, but also, at the same time, to be able to value in a more complete way, with other contextual factors, the current legislation. The work is divided into the three stages that seem to us to be most significant from the point of view of the studied regulation: the start of democracy, with the electoral regulations of the time, the Royal Law Decree 20/1977, of March 18 (indifference period); the period of Organic Law 5/1985, of June 19, of the General Electoral Regime, and the adjustments and complements of the immediately following years (period of visualization); and the normative advances made at the start of the twenty-first century, with the very relevant United Nations Convention on the Rights of Persons with Disabilities, and Royal Decree 422/2011, of March 25, approving the Regulation on the basic conditions for the participation of persons with disabilities in political life and in electoral processes (awareness period). This is followed by a brief final considerations, recapitulatory and prospective, the main of which is to highlight the constant and solid progression that has gradually been produced in this field with a final result that deserves to be recognized and estimated. It is also pointed out that most of the established normative actions operate in the area of active suffrage, leaving aside the right to passive suffrage and other forms of participation; That legislative attention to the various groups of people with disabilities has not been balanced either over time or in the final result, with greater attention being paid to the problem of people with physical and sensory disabilities (visual or auditory) than those with intellectual and psychic disabilities; And that many challenges remain, such as the limitation of the restriction of the vote of persons with intellectual and mental disabilities and the adoption of support measures in the field of passive suffrage.